Incidence and Management of Recurrence in Patients with Crohn's Disease Who Have Undergone Intestinal Resection: The Practicrohn Study. Issue 10 (October 2017) - Domènech, Eugeni; Garcia, Valle; Iborra, Marisa; Gutiérrez, Ana; García-López, Santiago; Martín Arranz, María D.; Garcia-Planella, Esther; Calvo, Marta; Castro, Luisa; Mínguez, Miguel; Taxonera, Carlos; Juliá, Berta; et al.
Abstract : Background: More than 50% of patients with Crohn's disease require intestinal resection at least once. Postoperative recurrence (POR) is almost uniform if prophylactic treatment is not started early. Endoscopic monitoring is generally advised. We studied the incidence and management of recurrence in patients who had undergone intestinal resection. Methods: Practicrohn was an observational retrospective study performed in 26 Spanish hospitals including patients aged ≥18 years who underwent Crohn's disease–related ileocolonic resection between January 2007 and December 2010. We recorded preventive treatments, the incidence of clinical recurrence in daily practice, and associated risk factors. Results: The study population comprised 314 patients. Median (interquartile range) time from diagnosis to surgery was 6 (1–12) years. Prophylaxis for POR was administered to 208 patients (68%). Endoscopy was performed in 143 (46%) patients the first year after surgery. Clinical POR was detected in 97 patients (31%) after a median 315 (65–748) days. The cumulative probability of clinical POR was 16%, 27%, and 31% at 1, 3, and 5 years, respectively, being higher among patients not receiving immunomodulators as compared to those who received prophylaxis ( P = 0.014). Forty-five patients (14%) required reoperation at 5 years after a median time from the first intervention of 228 (133–527) days. Conclusions: In this real-life study, up to one-third of patients with Crohn's disease did not start preventive therapy after intestinal resection, and almost half of them were not endoscopically monitored as recommended. In this setting, 30% of patients developed clinical POR within the first 5 years after surgery, thus indicating that there is room for improvement. Abstract : Article first published online 20 june 2017.